Multicellular thundercloud and interesting surface weather phenomena at Meenambakkam airfield on 15 July 1965 (MAUSAM, 1966)
A good example of the multicellular nature of a thundercloud as revealed by the interesting surface weather features over Meenambakkam airfield on 15 July 1965 is presented in this paper.